Altered amygdala DNA methylation mechanisms after adolescent alcohol exposure contribute to adult anxiety and alcohol drinking. (October 2019) - Sakharkar, Amul J.; Kyzar, Evan J.; Gavin, David P.; Zhang, Huaibo; Chen, Ying; Krishnan, Harish R.; Grayson, Dennis R.; Pandey, Subhash C.
Abstract: Binge drinking during adolescence increases the risk for neuropsychiatric disorders including alcoholism in adulthood. DNA methylation in post-mitotic neurons is an important epigenetic modification that plays a crucial role in neurodevelopment. We examined the effects of intermittent ethanol exposure during adolescence on adult behavior and whether DNA methylation changes provide a plausible explanation for the lasting effects of this developmental insult. One hour after last adolescent intermittent ethanol (AIE), growth arrest and DNA damage inducible protein 45 ( Gadd45a, Gadd45b, and Gadd45g ) mRNA expression was increased and DNA methyltransferase (DNMT) activity and Dnmt3b expression was decreased in the amygdala as compared to adolescent intermittent saline (AIS) rats. However, AIE rats 24 h after last exposure displayed increased DNMT activity but normalized Gadd45 and Dnmt3b mRNA expression compared to AIS rats. In adulthood, rats exposed to AIE show increased Dnmt3b mRNA expression and DNMT activity, along with decreased Gadd45g mRNA expression in the amygdala. DNA methylation of neuropeptide Y ( Npy ) and brain-derived neurotrophic factor ( Bdnf ) exon IV is increased in the AIE adult amygdala compared to AIS adult rats. Treatment with the DNMT inhibitor 5-azacytidine (5-azaC) at adulthood normalizes the AIE-induced DNA hypermethylation of Npy and Bdnf exon IV with concomitant reversal of AIE-induced anxiety-like and alcohol-drinking behaviors. These results suggest that binge-like ethanol exposure during adolescence leads to dysregulation in DNA methylation mechanisms in the amygdala which may contribute to behavioral phenotypes of anxiety and alcohol use in adulthood. Highlights: Adolescent intermittent ethanol (AIE) increases adult anxiety and alcohol drinking. AIE increased DMNT function in the amygdala in adulthood. AIE increased DNA methylation at Npy and Bdnf exon IV in the adult amygdala. 5-azacytidine treatment normalizes AIE-induced anxiety and alcohol consumption. 5-azacytidine treatment restores AIE-induced DNA hypermethylation at Npy and Bdnf .